Suffering and memory in Asian contexts and beyond: Towards a hermeneutical proposal for remembering comfort women in the future. Issue 4 (6th October 2021) - Lim, Sung Uk; Kuo, Henry S.
Abstract: How can we ensure that these important voices testifying to the memory of comfort women do not remain solely figments of local history, fixed within a certain time, to be gradually forgotten with each passing generation? In reflecting on this question, this study ventures the possibility of constructing a hermeneutical model that critically engages the memory of comfort women for the sake of all global citizens committed to resisting any types of violence, regardless of racial/ethnic and gendered boundaries. To do this, it proposes a hermeneutical model based on Kuan‐Hsing Chen's "Asia as method, " which places in conversation the theologies of Johann Baptist Metz and Angela Sims to read the memories of comfort women as dangerous memories that can remember a future of freedom from sexual violence, trauma, and militarism. The final result of the proposed hermeneutical model is to remember the testimonies of comfort women as dangerous memory for the global community, making them part of a global discourse that remembers them into different stories of suffering. Overall, the current project can readily address the implications of the proposed hermeneutical model to make comfort women's stories relevant to the present and future generations locally, nationally, and internationally, not only in terms of resistance to social sins such as sexual violence, but also in terms of fostering a spirit of solidarity with those in need of our support as a form of love.